2022
DOI: 10.1097/pap.0000000000000332
|View full text |Cite
|
Sign up to set email alerts
|

Chameleon TFE3-translocation RCC and How Gene Partners Can Change Morphology: Accurate Diagnosis Using Contemporary Modalities

Abstract: Translocation renal cell carcinoma (tRCC) with TFE3 gene rearrangements has been born as a distinct entity 20 years ago. These relatively rare tumors were notable among other RCC subtypes because of their disproportionally high incidence among children and young adults. Initial reports were focused on describing unifying morphologic criteria and typical clinical presentation. Follow-up studies of ancillary immunohistochemical and hybridization techniques provided additional diagnostic tools allowing recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…TRCC is a biologically heterogenous disease depending on fusion partners, which may have different impact on response to ICT combinations. 25 Data regarding the specific fusion partners were not available in our report; therefore, we were unable to assess their effect on outcomes. While we await the prospective data from AREN1721, our study suggests that ICT + VEGF TT regimens may yield higher clinical activity than dual ICT in adult patients with metastatic tRCC.…”
Section: Discussionmentioning
confidence: 95%
“…TRCC is a biologically heterogenous disease depending on fusion partners, which may have different impact on response to ICT combinations. 25 Data regarding the specific fusion partners were not available in our report; therefore, we were unable to assess their effect on outcomes. While we await the prospective data from AREN1721, our study suggests that ICT + VEGF TT regimens may yield higher clinical activity than dual ICT in adult patients with metastatic tRCC.…”
Section: Discussionmentioning
confidence: 95%
“…Although strong nuclear staining for TFE3 immunohistochemistry was initially reported as being highly sensitive and specific for TFE3-rearrangments, 13 subsequent studies have found its performance to be less reliable, leading to false-positive, false-negative, and equivocal results. 14,15 TFE3 immunoreactivity can be seen in other entities such as clear cell RCC and ALK-rearranged RCC. 10 Additionally, the sensitivity and specificity may vary depending on fixation time and use of different antigen retrieval methods or antibody clones.…”
Section: Discussionmentioning
confidence: 99%
“…87,88 However, cathepsin K is most useful in PRCC:: TFE3 and TFEB rearranged tumors, as most translocation RCC with other forms of gene rearrangements do not express this antigen. 50,51,88 In labs with limited resources, KRT7 and CA9 IHC may be extremely useful to distinguish TFE3 RCC from clear cell RCC (KRT7-/CA9 + ), clear cell papillary RCC (KRT7 + /CA9 + cup-shaped staining), papillary RCC (KRT7 + /CA9-) and chromophobe RCC (KRT7 + /CA9-) 14,86,89 in the differential diagnosis RCC with clear cell features, along with under-expression of pancytokeratins.…”
Section: Matr3:: Tfe3mentioning
confidence: 99%
“…In a recent review article, immunoprofile of nearly 400 TFE3 RCC cases were reviewed; most commonly expressed biomarkers were PAX8 (100%), TFE3 (95%), CD10 (89%), and racemase (82%); whereas KRT7 (10%), CA9 (3%), melan-A (17%), and HMB45 (19%) were usually negative. 86 They were repeatedly documented to have diminished staining with epithelial markers such as cytokeratins (ie cytokeratin AE1/AE3) and epithelial membrane antigen (EMA) but exceptions do exist. 14,85 Cathepsin K staining is highly specific for MiT translocation RCC.…”
Section: Clinicopathologic Features Of Tfe3 Rearranged Rccmentioning
confidence: 99%